Map of Oxnard, CA, with proposed LNG plant site and LNG Pipeline route
Single page document – undated map of Oxnard, CA, with proposed LNG plant site and LNG Pipeline route, school locations, non-hazardous industrial sites with 100+ employees, Potential hazardous industrial sites, existing high pressure gas lines, and railroad lines.